The Docking Protein HEF1 Is an Apoptotic Mediator at Focal Adhesion Sites - Law, Susan F. (American Society for Microbiology, 2000)
HEF1 (human enhancer of filamentation 1) is a member of a docking protein family that includes p130(Cas) and Efs. Through assembly of multiple protein interactions at focal adhesion sites, these proteins activate signaling cascades in response to integrin receptor binding of the extracellular matrix. The HEF1 protein is cell cycle regulated, with full-length forms cleaved in mitosis at a caspase consensus site to generate an amino-terminal 55-kDa form that localizes to the mitotic spindle. The identification of a caspase cleavage site in HEF1 led us to investigate whether HEF1 belongs to a select group of caspase substrates cleaved in apoptosis to promote the morphological changes characteristic of programmed cell death. Significantly, inducing expression of HEF1 in MCF-7 or HeLa cells causes extensive apoptosis, as assessed by multiple criteria. Endogenous HEF1 is cleaved into 65- and 55-kDa fragments and a newly detected 28-kDa form in response to the induction of apoptosis, paralleling cleavage of poly(ADP-ribose) polymerase and focal adhesion kinase (FAK); the death-promoting activity of over-expressed HEF1 is associated with production of the 28-kDa form. While the generation of the cleaved HEF1 forms is caspase dependent, the accumulation of HEF1 forms is further regulated by the proteasome, as the proteasome inhibitors N-acetyl-l-leucinyl-l-leucinyl-l-norleucinyl and lactacystin enhance their stability. Finally, the induction of HEF1 expression also increases Jun N-terminal protein kinase (JNK) activation, and activated JNK colocalizes with HEF1, implicating this pathway in HEF1 action. Based on these results, we propose that dysregulation of HEF1 and its family members along with FAK may signal the destruction of focal adhesion sites and regulate the onset of apoptosis.